An Android Mobile Application for Guide to Terrorism (International Journal of Engineering and Computer Science, 2018)
The way and manner the fundamentalist are penetrating our communities have posed serious threat to the populace, the government and the Army cannot be everywhere at the same time, the populace does not understand how to define terrorism due to its widely divergent views, the nature of terrorism, recognition of the terrorist and a terrorist threat is also not understood, properties and lives gone as a result of insurgency in the Northeastern part of Nigeria. This work is design to proffer instant reference guide and complement the Government and the Army to curb the activities of the terrorist and also to save lives. The designed, analysis and implementation were carried out using UML tools, Android studio (intelliJ platforms) and Java programming Language respectively. The application will serve as a reference guide for understanding terrorism and to allow the user to call or message the security personnel whenever there is an emergency using an android device as it will automatically show the user emergency number. When tested, the application have proven to guide and educate the populace on terrorism, it complements the government and the Army and also save lives and properties.